Tinjauan Pelaksanaan Ngukup Tirtha Dari Aspek Kimia Dan Kesehatan - Ni Ketut Sinarsih; Ni Made Umi Kartika Dewi; Ni Ketut Esati (Jurnal Yoga dan Kesehatan, 2023)
Tirtha is one of the elements that is always present in the Hindu religious ceremony. This paper aims to review the implementation of Ngukup Tirtha from a chemical and health perspective. This research is a descriptive review that was compiled based on studies and analysis of various online-based scientific articles, namely Google Scholar in 2017-2022 using the keywords Tirtha, water in Hinduism, Ngukup Tirtha, methods of sterilization, and water disinfection. The results of a review of various scientific articles show that water or equipment sterilization methods can be carried out using various methods including heating, steam or hot smoke, chlorination, ozonation, and using ultraviolet (UV) light. Ngukup is a process of preparing water for Tirtha by smoking water using frankincense or pasepan. Of these various methods, hot smoke or steam The method of sterilization with hot steam is identical to the process in Ngukup Tirtha in which the process uses hot smoke from burning some leaves and wood which gives aromas such as agarwood, sandalwood, pandan and others. The Ngukup Tirta process, in addition to providing advantages in the form of a fragrant aroma, can also improve the hygiene and sterility of the water used for Tirtha.